Clinical practice guidelines with recommendations for peripartum depression: A European systematic review. (24th August 2022) - Motrico, Emma; Moreno‐Peral, Patricia; Uriko, Kristiina; Hancheva, Camellia; Brekalo, Maja; Ajaz, Erilda; Apter, Gisele; Bramante, Alessandra; Conejo‐Cerón, Sonia; Christoforou, Andri; Dikmen‐Yildiz, Pelin; Evagorou, Olympia; et al.
Abstract: Objective: This study aims to systematically review all Clinical Practice Guidelines (CPGs) with recommendations for peripartum depression in European countries. Methods: A systematic review according to the PRISMA statement was conducted. CPGs focussing on peripartum depression or with at least one specific recommendation for peripartum depression from European countries were selected. Searching was conducted in electronic databases (MEDLINE and PsycINFO), and by contacting professional societies and international experts until November 24th, 2021. Characteristics of the included CPGs and their recommendations were extracted. A methodological quality assessment was conducted using the AGREE‐II tool. Results: A total of 239 records were identified after duplicate removal. Of these, 54 were examined for full‐text inspection. The final selection yielded 14 CPGs from 11 European countries in 10 languages. Of them, 11 provided recommendations on pharmacological treatments, 10 on psychological treatment (e.g., cognitive‐behavioural therapy), 10 on screening, 8 on diagnosis, 6 on other treatments (e.g., physical exercise), 5 on prevention, and 5 other recommendations (e.g., provide information). Regarding the overall methodological quality, only five (35.7%) guidelines were rated as of adequate quality, reaching a score ≥ 70% in the overall assessment of the AGREE‐II instrument. Of the six AGREE‐II domains, applicability scored the lowest and clarity of presentation scored the highest. Conclusion: The absence of CPGs in most European countries, the discrepancy in recommendations and the low methodological quality of the guidelines may lead to disparities and inequalities in peripartum depression management in Europe. The COST Action Riseup‐PPD highlights key considerations for future guideline developers.